THE DIALECTIC STUDY OF THE ENGLISH LANGUAGE IN THE LIGHT OF THE WORK "SCIENCE OF LOGIC" BY HEGEL: NEW DIALECTIC COGNITION, DIALECTICAL PROGRAMMING, AND THE PROCESSES OF THINKING - K. V. Molchanov (Российский технологический журнал)
The article discusses the dialectical study of the English language in the light of the work “Science of Logic” by Hegel. But this is not English language learning only - it is the study of this language in the wide sense. In the course of the study, some links between new dialectic cognition (including dialectical programming) and the English language were ascertained. The main result of our research is to identify the processes of thinking. The discussed provisions define the complex of issues relating to dialectical cognition. The results of the research can be used to develop epistemology, programming, linguistics, and psychology.